Dampak Pembelajaran di Rumah terhadap Kebiasaan Makan Selama Pandemi Covid-19 di Tanah Papua: Impact of Learning from Home on Food Patterns During Covid-19 Pandemic University Students in Papua - Ratih Nurani Sumardi; Nia Budhi Astuti; Sanya Anda Lusiana; Endah Sri Rahayu; I Rai Ngardita (Universitas Airlangga, 2023)
Background: In December 2019, the COVID-19 outbreak in Wuhan spread to 49 countries, including Indonesia. The government imposed a policy of learning at home for students. Due to activity restrictions, eating habits, and body weight changes have been reported in several countries. Objectives: This study aimed to see the impact of learning at home on changes in eating habits during the Covid-19 pandemic in Papua. Methods: The research design was cross-sectional, during June - July 2020, located in the Land of Papua (Papua and West Papua Provinces), Indonesia. Data was collected using Google Forms and shared through the WhatsApp group network. The analysis was carried out using non-parametric tests. The study was performed using non-parametric tests. Results: This study showed significant changes in food frequency during learning at home, dietary patterns, how to get food, fruit frequency intake, vegetable variations, and fruit variations. Conclusions: Learning at home during COVID-19 changed eating habits, including food frequency, dietary patterns, and fruit and vegetable variations. Although the variety of fruits and vegetables is declining, both are frequently increasing.